Investigation of the Mechanical, Electrical and Thermal Properties of Rubber Composites Filled with Various Carbon Nanomaterials, Carbon Nanotube, Graphene and Graphite - Kim, Sung-Woo; Jeong, Ho-Kyun; Kang, Yong-Gu; Han, Min-Hyeon (Asian Journal of Chemistry, 2013)
Rubber composites containing carbon black as a general fillers and multiwalled carbon nanotube, graphene and graphite as specific fillers were fabricated. Carbon materials were modified chemically and physically through an acid, heat and latex treatment to enhance the dispersion in rubber matrices. The acid, heat and latex treatment of carbon nanomaterials improved the mechanical properties, such as hardness, modulus, fatigue properties, electrical and thermal conductivity compared to pristine carbon materials. The modified graphene showed the most enhanced hardness, modulus and electrical conductivity but a significant decrease in the fatigue property and elongation. The modified carbon nanotube showed better thermal conductivity than the others, whereas the electrical and thermal conductivity of the nanocomposites decreased due to the formation of surface defects of multiwalled carbon nanotube by chopping.